(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: The creative poetic text is a text that is open to many readings, a text that includes dense connotations. It suggests meanings that vary in clarity, because it is a text that rejects vulgarity and refuses to reveal a final meaning that can be ascertained, Muhammad Al-Mazwghi poetry abounds in many creative manifestations, including the openness of the text to horizons and substances that make the recipient interact with the poetic text, and not tire of hearing or reading it. Because each time he discovers what leads him to a new understanding, unique connotations, and revelations that reveal meanings from a different, unexpected angle. Through this interpretive reading, which is based on an analytical approach based on linguistic and social data, it helps to count the expected connotations, interpret the implicit meanings, and reveal the hidden intent behind the literary work.